The influence of emotional picture thematic content on exploratory eye movements - Elena Carniglia; Marcella Caputi; Valentina Manfredi; Daniela Zambarbieri; Eliano Pessa (Bern Open Publishing, 2012)
In picture viewing, emotional vs. neutral stimuli could play a different role in eye movement parameters and in the spatial progression of the scanpath. The aim of this paper is to investigate exploratory behaviour of normal subjects during the vision of emotional vs. non-emotional stimuli, by considering to what extent the thematic content (animate vs. inanimate) is likely to influence the observer's eye movements. Sixty-five subjects' eye movement patterns were measured while looking to emotional (pleasant and unpleasant) and neutral pictures depicting animate or inanimate contents. Results showed that the number of fixations and the gaze duration were greater for emotional pictures than for neutral ones, and animate pictures were fixated longer than inanimate ones. Both emotional and animate pictures may affect eye movements and constitute privileged stimuli of adaptive behavioural tendencies.